La polifarmacia y sus principales efectos adversos en los adultos mayores que acuden al centro de atención del adulto mayor del Instituto Ecuatoriano de Seguridad Social durante el periodo mayo - diciembre 2015. - Calva Ochoa, Karen Jackeline (2016)
It was defined as polypharmacy the intake of 3 or more medicines. Polypharmacy represents a health risk, especially in older adults, since with the aging dissemination, distribution and particularly the elimination of medicinal products decreases with age, hence its prevalence is significantly higher in this age group. The main objective of the present investigation was: To investigate polypharmacy and its main adverse effects in older adults who come to the Center of Attention of the Elderly of the Ecuadorian Institute of Security during the period May to December 2015. In addition, the stated objectives are: To determine the most frequent polypathology, To determine the polypharmacy and the medicines that they frequently consume, To identify the major adverse effects of polypharmacy and To relate polypharmacy to adverse effects in older adults who come to the Center of Attention of the Elderly of the Ecuadorian Institute of Social Security. A cross-sectional descriptive study was conducted, in a sample of 120 older adults, which were surveyed to know how many consume 3 or more medications per day. It was found that polypharmacy was present in 100% of the older adults, the medicines that they consume more were: the vitamins (18.78%), the Antihypertensive drugs (17.76%) and the hypoglycemic agents (12,24). The most frequent diseases where the Endocrine Metabolic (30.42%), followed by the Cardiovascular (26,57) and the Osteoarticular (17,13%). The major adverse effects where the Gastric discomfort (32,62%), tiredness (14,44%), constipation (13,90%). It is concluded that the most frequent pathologies in older adults where the Endocrine Metabolic, the cardiovascular and the Osteoarticular ones. The drugs that they take more commonly are the vitamins, the antihypertensive drugs and the hypoglycemic agents KEY WORDS: older adult, polypharmacy, adverse drug reactions